The transcription factor IRF4 is essential for TCR affinity–mediated metabolic programming and clonal expansion of T cells - Man, Kevin; Miasari, Maria; Shi, Wei; Xin, Annie; Henstridge, Darren C; Preston, Simon; Pellegrini, Marc; Belz, Gabrielle T; Smyth, Gordon K; Febbraio, Mark A; Nutt, Stephen L; Kallies, Axel (Nature immunology, 2013)
Clonal expansion of cytotoxic T lymphocytes entails profound energetic demands. Kallies and colleagues show that the transcription factor IRF4 is critical for the metabolic reprogramming, survival and effector function of these cells during clonal expansion. During immune responses, T cells are subject to clonal competition, which leads to the predominant expansion of high-affinity clones; however, there is little understanding of how this process is controlled. We found here that the transcription factor IRF4 was induced in a manner dependent on affinity for the T cell antigen receptor (TCR) and acted as a dose-dependent regulator of the metabolic function of activated T cells. IRF4 regulated the expression of key molecules required for the aerobic glycolysis of effector T cells and was essential for the clonal expansion and maintenance of effector function of antigen-specific CD8 + T cells. Thus, IRF4 is an indispensable molecular 'rheostat' that 'translates' TCR affinity into the appropriate transcriptional programs that link metabolic function with the clonal selection and effector differentiation of T cells.